2013
DOI: 10.1371/journal.pone.0075382
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing Patterns among Black Men Who Have Sex with Men: A Qualitative Typology

Abstract: BackgroundBlack men who have sex with men (MSM) in the Southeastern United States are disproportionately affected by HIV. Black MSM are more likely to have unrecognized HIV infection, suggesting that testing may occur later and/or infrequently relative to current recommendations. The objective of this qualitative study was to explore the HIV testing behaviors of Black MSM in Atlanta, Georgia, who were participants in the HIV Prevention Trials Network Brothers Study (HPTN 061).Methods and FindingsWe conducted 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Other dimensions of diversity pertinent to consider in the development of interventions targeted toward BMSM include HIV testing patterns and HIV status disclosure (Bird amp; Voisin, 2013; Harawa, Williams, Ramamurthi, amp; Bingham, 2006; Hussen et al, 2013; Lichtenstein, 2000; Miller, 2007; Wheeler, 2005; Williams et al, 2004), age (Eyre, Milbrath amp; Peacock, 2007; Haile, Padilla amp; Parker, 2011; VenDevanter et al, 2011), and drug use (Jerome amp; Halkitis, 2009; Washington amp; Brocato, 2011; Washington amp; Meyer-Adams, 2010; Wilton et al, 2005; Wu, El-Bassel, McVinney, Fontaine, amp; Hess, 2010). Several studies explicitly noted that interventions need to be cognizant that there is no one “type” of BMSM and therefore narrowly-focused interventions will be limited in their impacts (Arnold amp; Bailey, 2009; Fields et al, 2015; Hightow-Weidman et al, 2011; Hussen et al, 2013; Washington amp; Brocato, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other dimensions of diversity pertinent to consider in the development of interventions targeted toward BMSM include HIV testing patterns and HIV status disclosure (Bird amp; Voisin, 2013; Harawa, Williams, Ramamurthi, amp; Bingham, 2006; Hussen et al, 2013; Lichtenstein, 2000; Miller, 2007; Wheeler, 2005; Williams et al, 2004), age (Eyre, Milbrath amp; Peacock, 2007; Haile, Padilla amp; Parker, 2011; VenDevanter et al, 2011), and drug use (Jerome amp; Halkitis, 2009; Washington amp; Brocato, 2011; Washington amp; Meyer-Adams, 2010; Wilton et al, 2005; Wu, El-Bassel, McVinney, Fontaine, amp; Hess, 2010). Several studies explicitly noted that interventions need to be cognizant that there is no one “type” of BMSM and therefore narrowly-focused interventions will be limited in their impacts (Arnold amp; Bailey, 2009; Fields et al, 2015; Hightow-Weidman et al, 2011; Hussen et al, 2013; Washington amp; Brocato, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies explicitly noted that interventions need to be cognizant that there is no one “type” of BMSM and therefore narrowly-focused interventions will be limited in their impacts (Arnold amp; Bailey, 2009; Fields et al, 2015; Hightow-Weidman et al, 2011; Hussen et al, 2013; Washington amp; Brocato, 2011). …”
Section: Resultsmentioning
confidence: 99%
“…Only 67 % of HIV-negative BMSM in one study were tested for HIV in the last 2 years [27] and only 52 % in another study were tested in the last year [28]. Other findings highlight the heterogeneity of HIV testing patterns among BMSM [29]. HIV-infected BMSM are also less likely than other HIV-infected MSM to be aware of their positive serostatus [10, 30–32].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found high HIV infection rates, particularly among young African American MSM [5, 6]. HIV prevention research has shown that high rates of HIV among African American MSM may in part be attributed to younger sexual debut [7], older sexual partners [8], sexually transmitted infection (STI) rates, sexual mixing within African American networks that facilitate HIV transmission [811], infrequent HIV testing [12], and undetected or late diagnosis of HIV infection [13, 14]. These issues are compounded by African American MSM poor access to quality medical care and HIV antiretroviral therapies [15, 16].…”
Section: Introductionmentioning
confidence: 99%